2012
DOI: 10.1152/jn.00723.2011
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of cortical neural variability is stimulus- and state-dependent

Abstract: Internally generated, spontaneous activity is ubiquitous in the cortex, yet it does not appear to have a significant negative impact on sensory processing. Various studies have found that stimulus onset reduces the variability of cortical responses, but the characteristics of this suppression remained unexplored. By recording multiunit activity from awake and anesthetized rats, we investigated whether and how this noise suppression depends on properties of the stimulus and on the state of the cortex. In agreem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 36 publications
6
42
3
Order By: Relevance
“…These results are in agreement with recent reports (He, 2013) of a reduction in variability in the fMRI BOLD signals following stimulus onset, as well as with animal studies that showed that intrinsically generated spontaneous fluctuations in neuronal activity undergo suppression during task-evoked activity throughout the cortex in a broad range of conditions (White, Abbott, & Fiser, 2012;Churchland et al, 2010;Churchland, Yu, Ryu, Santhanam, & Shenoy, 2006). The decline in variability implies that cortical circuits can be stabilized by an input or a task and may support information encoding (He, 2013;White et al, 2012;Churchland et al, 2010). In the current study, however, the large decreases in the M1 signal variability with task performance were not differentially modulated by the level of experience with the specific movement sequence or by its repetition across the brief rest interval.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with recent reports (He, 2013) of a reduction in variability in the fMRI BOLD signals following stimulus onset, as well as with animal studies that showed that intrinsically generated spontaneous fluctuations in neuronal activity undergo suppression during task-evoked activity throughout the cortex in a broad range of conditions (White, Abbott, & Fiser, 2012;Churchland et al, 2010;Churchland, Yu, Ryu, Santhanam, & Shenoy, 2006). The decline in variability implies that cortical circuits can be stabilized by an input or a task and may support information encoding (He, 2013;White et al, 2012;Churchland et al, 2010). In the current study, however, the large decreases in the M1 signal variability with task performance were not differentially modulated by the level of experience with the specific movement sequence or by its repetition across the brief rest interval.…”
Section: Discussionsupporting
confidence: 93%
“…Variability reduction following stimulus onset was previously reported in neuronal firing (Werner and Mountcastle, 1963; Churchland et al, 2010; Chang et al, 2012; White et al, 2012). However, given the complex relationships between the fMRI signal, neuronal firing and local field potentials (LFP) and the dissociation between the fMRI signal and neuronal firing under various conditions (e.g., Logothetis, 2008; Maier et al, 2008; He and Raichle, 2009), our finding of variability reduction in the fMRI signal does not follow trivially from this previous work.…”
Section: Discussionsupporting
confidence: 53%
“…Finally, we note that the variability of membrane potential, synaptic excitation and inhibition also depends on sensory stimulus and cortical area (Heil, 1997; Stiebler et al, 1997; DeWeese et al, 2003; Monier et al, 2003; Tan et al, 2004, 2007; Finn et al, 2007; Gutnisky and Dragoi, 2008; Herikstad et al, 2011; Hansen et al, 2012; White et al, 2012). The covariability of excitation and inhibition should therefore also be measured for different sensory stimuli in different cortical areas.…”
Section: Discussionmentioning
confidence: 90%